Field evaluation of Standard Q Filariasis Antigen Test for Lymphatic Filariasis (LF) during a pre-transmission assessment survey in Sierra Leone, 2022. - Benoit Dembele; Mohamed Salieu Bah; Abdulai Conteh; Habib I Kamara; Ibrahim Kargbo-Labour; Ashley Souza; Patricia Houck; Ernest O Mensah; Victoria Turay; Eric Scott Elder; Katherine Gass; Steven D Reid; et al. (PLoS Neglected Tropical Diseases)
Background As part of a multi-country evaluation, the SD Biosensor STANDARD Q Filariasis Antigen Test (QFAT) was compared with the Abbott Bioline Filariasis Test Strip (FTS) for assessing Wuchereria bancrofti infection prevalence and for ease of use of QFAT in field conditions in Sierra Leone. Methods and principal findings The evaluation was done in two districts, Bombali and Karene, where repeat pre-transmission assessment surveys (pre-TAS) were planned. Two rural sites, Kagbo and Makorba Yelimini which recorded high LF antigen prevalence of 4.1% and 7.7% respectively in repeat pre-TAS in 2020 were selected for the QFAT evaluation. At least 350 people ≥5 years were targeted per site for inclusion in the study by convenience sampling. Blood was collected by fingerstick; 20μl for QFAT and 75μl for FTS. The reading time for both tests was 10 minutes. For all positive or invalid results, a repeat test was performed for both tests. In total, 728 participants (5-91 years) were tested by QFAT and FTS. Four FTS and three QFAT final results were classified as indeterminate (meaning a positive result followed by a negative result) and were excluded from the analysis. The positive rate was 4.8% (17/357) and 3.5% (13/367) for FTS and 3.4% (12/359) and 4.1% (15/366) for QFAT in Kagbo and Makorba Yelimi, respectively. All participants testing positive for FTS or QFAT underwent further testing by night blood smear to detect microfilariae using microscopy. No W. bancrofti microfilariae was detected in any of the antigen positive cases. In field conditions, QFAT was easy to handle and recorded zero invalid tests compared to FTS (six invalids). The concordance between FTS and QFAT was 0.81 (Cohen's Kappa). The discrepancy found between the two tests in terms of positive tests was not statistically significant (p = 0.78). Conclusions/significance The results suggest that the QFAT is a credible W. bancrofti diagnostic test when compared to the routinely used FTS; use of either test would result in the same program decision.